PENGARUH LATIHAN SENAM BUGAR LANSIA TERHADAP MENOPAUSE RATING SCALE (MRS) PADA WANITA MADYA LANSIA PANTI WERDHA SURYA SURABAYA - Farisin, Mohammad Syaiful (Jurnal Kesehatan Olahraga, 2018)
Menopause is a stage that shows the end of a woman's ability to reproduce. This study was conducted to determine the effect of elderly gymnastics exercise on middle aged women in Menopause Rating Scale (MRS) at Panti Werdha Surya Surabaya. The type of research used is the type of quantitative research using a quasi-experimental approach. The object of research is 20 people, using population research (all objects are sampled). This study used questionnaires and interview guides by filling out questionnaires before and after doing gymnastics fit then the researchers calculate the percentage of MRS is then categorized according to the symptoms that occur. From the results of research conducted for 6 weeks located in Panti Werdha Surya Surabaya The results of data calculations that there are 15 (34.09%) of respondents who experience severe symptoms before following elderly gymnastics. The result of calculation of respondent data after following elderly gymnastics found 3 (6.81%) of respondents who have followed elderly gymnastics for 1 year including heavy symptom category. There are 5 (11,36%) of respondents having symptoms of intermediate before joining elderly gymnastics and after following elderly gymnastics there are 14 (31,81%) of respondents who have been following elderly gymnastics for 1-3 years. The number of respondents categorized in mild symptoms before following elderly gymnastics was 0 (0%) respondents and after following elderly gymnastic during 1-4 years, the number of respondents who experienced mild symptoms to 3 (6.81%) of respondents. From the above data it can be concluded that elderly gymnastics can reduce the symptoms in women who face pre-menopause and menopause in middle-aged women at Panti Werdha Surya Surabaya.Keywords: Menopause Rating Scale (MRS), Senam Bugar Lansia.